2016
DOI: 10.15252/embj.201694572
|View full text |Cite
|
Sign up to set email alerts
|

Gata6 promotes hair follicle progenitor cell renewal by genome maintenance during proliferation

Abstract: Cell proliferation is essential to rapid tissue growth and repair, but can result in replication-associated genome damage. Here, we implicate the transcription factor Gata6 in adult mouse hair follicle regeneration where it controls the renewal of rapidly proliferating epithelial (matrix) progenitors and hence the extent of production of terminally differentiated lineages. We find that Gata6 protects against DNA damage associated with proliferation, thus preventing cell cycle arrest and apoptosis. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 115 publications
(169 reference statements)
5
46
1
Order By: Relevance
“…Only bulge HF‐SCs exhibited reduced c‐JUN/JUNB expression, while basal and suprabasal ORS layers in the sub‐bulge and proximal bulb regions maintained the expression of c‐JUN/JUNB (Fig EV1B and C). In addition, other regulators of HF‐SC renewal from other regions in the hair follicle, such as GATA‐6, expressed in progenitor matrix cells (bulb) in mice were analyzed (Wang et al , ). Interestingly, GATA‐6 was up‐regulated in suprabasal ORS layers in the bulge region from psoriatic lesional scalps, while no differences were observed in GATA‐6‐positive cells from the proximal bulb (Fig EV1C).…”
Section: Resultsmentioning
confidence: 99%
“…Only bulge HF‐SCs exhibited reduced c‐JUN/JUNB expression, while basal and suprabasal ORS layers in the sub‐bulge and proximal bulb regions maintained the expression of c‐JUN/JUNB (Fig EV1B and C). In addition, other regulators of HF‐SC renewal from other regions in the hair follicle, such as GATA‐6, expressed in progenitor matrix cells (bulb) in mice were analyzed (Wang et al , ). Interestingly, GATA‐6 was up‐regulated in suprabasal ORS layers in the bulge region from psoriatic lesional scalps, while no differences were observed in GATA‐6‐positive cells from the proximal bulb (Fig EV1C).…”
Section: Resultsmentioning
confidence: 99%
“…cDNA synthesis and qRT-PCR was performed as described earlier (45). Primers used are listed in Supplementary Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Response factors were calculated with an external standard mixture (GLC462; Nu-Chek Prep, Inc.) and applied to raw areas to correct for differential instrument responses. Percentages of each fatty acid were calculated by dividing the corrected area of individual fatty acid by the corrected area of total fatty acids for each lipid class (45). …”
Section: Methodsmentioning
confidence: 99%
“…Gene expression experiments further showed that Lrig1 and K79 message levels correlate with that of Gata6 , which encodes a zinc finger transcription factor that plays multiple key roles during development . Deletion of Gata6 has been reported to stifle hair regeneration by causing replicative stress in fast‐cycling matrix progenitor cells and can also lead to a reduction in upper hair follicle cells that ordinarily express this protein . Morphological defects in the upper hair follicle, however, have not been described in these mutants.…”
Section: Introductionmentioning
confidence: 99%